UTILIZING ENGLISH SONGS AS MEDIA TO ENHANCE STUDENTS’ QUALITY OF PRONUNCIATION IN SMP MUHAMMADIYAH 3 BONTOALA (Karya Ilmiah Mahasiswa (KIMA), 2022)
This research focused on utilizing English songs as media to enhance students' pronunciation. The objectives of this study were to the extent of the effects of using English songs in improving students' pronunciation ability and to find out the kinds of problems that students faced when they learned English pronunciation through the English songs. The method used was an experiment with quantitative and qualitative approaches. The research instrument consisted of two kinds, namely pronunciation tests, and questionnaires. The subjects of this study were 34 students in the first year of SMP Muhammadiyah 3 Bontoala in the academic year 2021/2022. In this research, students' pronunciation test scores were calculated using the SPSS 25. The results showed that students' achievement in pronouncing English words increased. This can be seen in the mean score of students on the pre-test which only reached 45.3 while after being given treatment four times, after being tested the mean score of their post-test increased to 61.6. This showed a significant increase so this method was effective in improving students' English pronunciation. Meanwhile, the results of the questionnaire showed that students really enjoyed learning English by using songs even though they still had some problems such as shy or afraid, there were still unfamiliar words, and the duration of learning English was limited.  So, the writer concluded that the use of the songs as the English learning media was effective.